Why, how and when do children die in a Paediatric Intensive Care Unit (PICU) in South Africa? - Wege, Martha Helena (Department of Paediatrics and Child Health, 2020)
Objectives: To describe the characteristics of children who died and their modes of dying in a South African Paediatric Intensive Care Unit (PICU). Design: Retrospective review of data extracted from the Child Healthcare Problem Identification Programme (Child PIP)and the PICU summary system (admission and death records) on children of any age who died in the PICU between 01 January 2013 and 31 December 2017. Setting: Single-centre tertiary institution. Patients: All children who died during PICU admission were included. Measurements and Main Results: Four-hundred and fifty-one (54% male; median (IQR) age 7 (1-30) months) patients died in PICU on median (IQR) 3 (1-7) days after PICU admission; 103 (22.8%) had a cardiac arrest prior to PICU admission. Mode of death in 23.7% (n=107) was withdrawal of life sustaining therapies; 36.1% (n=163) died after limitation of life sustaining therapies; 22.0% (n=99) died after failed resuscitation and 17.3% (n=78) were diagnosed brain dead. Ultimately, 270 (60%) children died after the decision to limit or withdraw life sustaining therapies. There was no difference in the number of deaths during office and after-hours periods (45.5% vs. 54%; p = 0.07). Severe sepsis (21.9%) was the most common condition associated with death, followed by cardiac disease (18.6%).Ninety-four (20.8%) patients were readmitted to the PICU within the same year; 278 (61.6%) had complex chronic disorders. During the last phase of life, 75.0% (n=342) were on inotropes, 95.9% (n=428) were ventilated, 12.0% (n=45) received inhaled nitric oxide and 10.8% (n=46) renal replacement therapy. Only 1.5% (n=7) of children became organ donors and postmortems were done in 47.2% (n=213) of the patients. Conclusions: Most PICU deaths occurred after a decision to limit or withdraw life-sustaining therapy. Severe sepsis was the most common condition associated with death. Referral for organ donation was extremely rare.